Early assessment of visual outcomes and corneal stability in eyes with a pre-planned residual stromal thickness of 280 to 300 μm following small incision lenticule extraction - Yin Liu; Jian-Min Shang; Cheng Hu; Xiao Chen; Wen-Shan Jiang; Jia Huang (International Journal of Ophthalmology)
AIM: To assess early visual outcomes and corneal stability following small incision lenticule extraction (SMILE) in eyes with a pre-planned residual stromal thickness (RST) ranging from 280 to 300 μm. METHODS: This retrospective study was designed to evaluate 82 eyes from 82 patients, all of whom had a pre-planned RST of 280 to 300 μm and normal corneal topography prior to undergoing SMILE surgery. The mean preoperative spherical equivalent (SE) was -4.82±1.30 D. A standard follow-up protocol was conducted between 1 to 6mo postoperatively. Visual outcomes were recorded using uncorrected visual acuity (UCVA) and subjective refraction. The curvature of the anterior and posterior corneal surfaces, as well as the posterior elevation at the thinnest point (PTE) were derived from the Pentacam system. RESULTS: At the final follow-up, the efficacy index was 1.14±0.15, the safety index was 1.20±0.13. The mean preoperative UDVA was 0.78±0.16 logMAR, which improved significantly to -0.07±0.06 logMAR postoperatively (P<0.001). The preoperative mean SE was -4.82±1.30 D, which decreased to -0.14±0.30 D by the last visit. The curvature of the anterior cornea at the flat meridian (AK1) were 42.62±1.02 D preoperatively, 38.56±1.37 D and 38.59±1.39 D at 1 and 6mo after operation, respectively. Corresponding measurements at the steep meridian (AK2) were 43.55±1.14 D preoperatively, 39.18±1.46 D and 39.22±1.50 D at 1 and 6mo after operation, respectively. Both AK1 and AK2 remained stable at 1 and 6-mo postoperative intervals (P=0.126 and 0.082, respectively). There were no observed changes in the curvature of the posterior cornea at the flat meridian or at the steep meridian, or the PTE before and after surgery. CONCLUSION: SMILE represents a safe and effective procedure for the correction of myopia and astigmatism in eyes featuring a pre-planned RST ranging from 280 to 300 μm accompanied by normal corneal topography, on the premise of strict control of surgical indications.